Preventing sexual violence in sport: Determinants of positive coach-bystander behavior - Verhelle, Helena; Vertommen, Tine; Peters, Gjalt-Jorn Ygram (Frontiers in Psychology, 2022)
Given their central role and position, coaches are instrumental in creating safe sport environments, especially in preventing sexual violence, but little is known about bystander behaviors, hampering the development of effective bystander programs in the context of sport. To identify determining characteristics of bystander behavior, 1,442 Belgian youth sport coaches completed an online questionnaire on bystander-related attitudes, norms, autonomy beliefs, and self-efficacy using two hypothetical scenarios of sexual violence in the sports club. Data were analyzed using confidence interval-based estimation of relevance (CIBER). A total of 127 coaches had witnessed sexual violence over the past year, most but not all intervened. Experiential attitude expectation, instrumental attitude evaluation, perceived referent behavior and approval, and subskill presence were positively associated with coaches’ intention to intervene. Of the determinants of positive coach-bystander behavior, attitude and perceived norms proved key constituents for programs addressing sexual violence in youth sport. We conclude that interventions aiming at increasing positive affective consequences, reinforcing the sense of group membership, and strengthening the social norm of intervening in case of signs of sexual violence may be most influential to stimulate positive coach-bystander behavior.